Analysis of Spelling Errors in Popular Scientific Articles: A Case Study of Grade XII Students of SMAN 6 Solok Selatan - Regi Alveri Hendra; Yulia Sri Hartati; Upit Yulianti DN (Jurnal Bebasan, 2024)
This study aims to identify and analyze common spelling errors in popular scientific articles written by grade XII students at SMAN 6 Solok Selatan. By analyzing the articles that have been created, this study categorizes various types of spelling errors. This research method involves a qualitative analysis of 33 scientific articles written by students, focusing on the most frequently occurring spelling errors. The main findings indicate that the most common spelling errors include capitalization, spelling errors, and punctuation errors. This study makes an important contribution to understanding the challenges faced by students in scientific writing, as well as providing practical recommendations for improvement in Indonesian language learning in senior high schools. The results of this study are expected to assist teachers and curriculum developers in designing more effective teaching strategies to improve students' scientific writing skills. The findings of this study are expected to provide useful insights for improving Indonesian language learning at the senior high school level and provide concrete recommendations for students and educators to improve spelling accuracy in scientific writing.